Comparison study on platinum decorated bismuth tungstate graphitic carbon nitride under batchwise and one step preparation techniques for photodegradation of RR4 dye / Qoid Syauqi Syahid Mohammed - Mohammed, Qoid Syauqi Syahid
The fabrication of Z-Scheme heterojunction comprising photocatalysts Bi2WO6 & g-C3N4 doped with platinum was successfully synthesized by two distinctive methods; batchwise & one-step to degrade model pollutant, RR4 dye. In batchwise method, Bi2WO6 is combined with g-C3N4 prior incorporating platinum into the composite. Whereas, for one-preparation technique Bi2WO6 is calcined first with platinum before the construction of z-scheme heterojunction with g-C3N4. RR4 were used as model pollutant to measure the photocatalytic performance of pt-Bi2WO6/g-C3N4. Characterization study employing FTIR, UV-Vis spectra, FESEM-EDX and XRD was conducted to characterized the composite. Based on the FTIR analysis aromatic C-N stretching vibration mode is detected in the region of 1200–1750 cm−1. In addition, intense sharp peak appear around 810 cm−1 is attributed to the breathing mode striazine units of CN. Further, in UV-Vis analysis, pristine Bi2WO6 has an absorption edge of approximately detected at 443 nm, which corresponds to a band gap of approximately 2.6 eV. The absorption edge of pure g-C3N4 was at about 457 nm, corresponding to the band gap of 2.8 eV. The fabrication of heterojunction of the composite results in gradual red-shift and the introduction of platinum results in even lower the band gap energy. The crystallinity size of the prepared photocatalysts was determined by XRD diffraction where Scherrer equation is applied to calculate the size magnitude In XRD, the diffraction angle of Bi2WO6 exhibits at 28.6⁰, 33.1̊, 47.4⁰, 56.2⁰ ,59.1⁰,69.2⁰ and 78.8⁰ and these diffraction angle also can be seen on the other composite. All of the modified and unmodified Bi2WO6/g-C3N4 have shown photocatalytic degradation efficiency up to 50% and the composite prepared by the means of one step offers the outstanding performance achiving 80% photodegradation activity of RR4 dye.